The aesthetic management of gingival enlargement and hyperpigmentation in maxillary anterior region: a case report - Kurnia, Shafira (Hasanuddin University, 2019)
Objective: To describe the aesthetic treatment stage of gingival enlargement with gingival hyperpigmentation. Determination of the type of action detail will assist many clinicians in diagnosis and treat gingival enlargement with hyperpigmentation.Methods: The 17-year-old male patient, coming with his enlarged gums. Patients claimed to have no hypertension, blood disorders, diabetes and hepatitis. After general check-up and early treatment, gingivectomy and gingival depigmentation were performed using scalpel no. 15c. The oral administration administered was 500mg tid amoxicillin and 500mg tid.prn mefenamic acid.Results: after gingivectomy has performed multiple diastema appears and suggested orthodontia treatment. Conclusion: The combination of gingivectomy treatment with gingival depigmentation may be performed simultaneously using a scalpel periodontal instrument.Keywords: Gingival enlargement, Gingival hyperpigmentation, Gingivectomy, Gingival depigmentation